Functionalized dual modification of covalent organic framework for efficient and rapid trace heavy metals removal from drinking water. (March 2022) - Yang, Yanan; Zhang, Yu; Zheng, Hong; Zhang, Baichao; Zuo, Qi; Fan, Kaiyue
Abstract: A key challenge in trace heavy metals removal from drinking water by adsorption technology is to achieve high adsorption capacity and rapid uptake speed of adsorbent. Herein, we report a functionalized double modified covalent organic framework (DMTD–COF–SH) bearing high-density sulfur and nitrogen chelating groups provided simultaneously by 2, 5-dimercapto-1, 3, 4-thiadiazole (DMTD) and 1, 2-ethanedithiol, which was prepared via a facile one-pot thiol-ene "click" reaction. PXRD, FTIR, XPS, SEM, BET and 13 C MAS NMR confirmed their successful graft, and DMTD was found to be more easily grafted on the COF surface layer than 1, 2-ethanedithiol. The as-prepared DMTD–COF–SH showed remarkable adsorption capacity and ultrafast uptake dynamics to trace heavy metals owing to the synergistic effects resulting from densely populated sulfur and nitrogen chelating groups within ordered COF mesopores and at the COF surface. On the basis of the drinking water treatment units standard NSF/ANSI 53–2020, when the adsorbent dosage was 10 mg/30 mL and 20 mg L −1 calcium ions coexisted, the lead concentration decreased from initial 150 μg L −1 to 2.89 μg L −1 within 10 s, far below the allowable limit of world health organization (WHO) drinking water standard (10 μg L −1 ), and the maximum adsorption capacity meeting the standard attained 14.22 mg g −1 . The adsorbent also exhibited excellent stability, wide applicable pH range and outstanding adsorption performance for coexisting trace lead, mercury, cadmium, chromium (VI) and copper in tap water, indicating that the DMTD–COF–SH material has excellent application prospect for trace heavy metals removal from drinking water. Graphical abstract: Image 1 Highlights: COF–V was successfully double modified by DMTD and ethanedithiol via a facile method. DMTD–COF–SH contains high-density S and N chelating groups with strong affinity. DMTD–COF–SH shows ultrafast uptake speed, large uptake capacity and good stability. DMTD–COF–SH shows good removal performance for multiple coexisting trace heavy metals. DMTD–COF–SH shows wide applicable pH range and excellent application prospect.